Generation Z’s perceptions of celebrity divorce on social media - Rianda Abdi; Suci Fitrah Syari; Alfiesyahrianta Habibie (Priviet Social Sciences Journal, 2026)
The phenomenon of celebrity divorce has become a highly discussed topic on social media, transforming from a private matter into a public phenomenon observed and internalized by young audiences. This study aims to understand how Generation Z interprets celebrity divorce news on social media and how such continuous exposure shapes their perceptions of marriage. Grounded in Albert Bandura’s Social Learning Theory, this research utilizes a qualitative phenomenological approach to explore these cognitive processes. Data were collected through in-depth interviews with ten unmarried Generation Z informants (aged 19–28) who actively consume celebrity news. Data analysis followed Creswell’s thematic stages. The findings reveal that Generation Z engages in observational learning by treating celebrities as symbolic models. Instead of imitating negative behaviors, informants practice selective modeling by adopting relational values they consider positive and ethical. Furthermore, social media comment sections function as vicarious reinforcement, offering moral validation that influences their assessment of relational ethics. The study also highlights the emergence of self-regulation in managing toxic media exposure, which contributes to a significant shift in their marriage values from romantic idealism to critical realism. These insights emphasize the need for strengthening critical digital literacy, safe-relationship education, and collaborative policies to promote healthier social norms.